Clear Cell Renal Cell Carcinoma 2021-2022 - Manini, Claudia; López, José I. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Clear cell renal cell carcinoma is currently one of the most interesting areas of study in oncology. Despite the advances made in this field, this tumor continues to be a health problem of major concern in Western societies, seriously affecting public health services. Several characteristics of this tumor make it an exciting meeting point for translational collaboration between clinicians and basic researchers. Clear cell renal cell carcinoma is a paradigmatic example of inter- and intra-tumor heterogeneity from morphological, immunohistochemical, and molecular viewpoints. This tumor is also a good example to investigate the complexity of tumor/tumor and tumor/environment relationships from an ecological perspective. A deeper identification of the varied internal tumor self-organization through the specialization of cell clones and subclones as local invaders and metastasizers, on one hand, and the interactions of specific subsets of tumor cells with the local host microenvironment, on the other, will significantly enrich our knowledge of this neoplasm. Clear cell renal cell carcinoma is also a paradigmatic test bench for antiangiogenic and immune checkpoint blockage therapies. The refinement of these therapeutic tools administered alone or in combination is a hot issue in oncology, and several international trials are underway.